Accounting Reserves as an Instrument of Reducing the Economic Risks of Catering Organizations - Taya Denisova; Maksim Gvozdev; Yulia Markina; Marina Bazhanova (Communications of International Proceedings, 2020)
The article describes the implementation of the main principle of the activity of catering enterprises, or any other company for that matter – the continuity principle. The factors influencing the continuity of business are considered. The authors analyse the ways of managing and reducing the economic risks of catering enterprises. The authors propose a method of provisioning as the most efficient way to reduce the economic risk. For the business activity of enterprises to remain continuous, it has been suggested to create a complex of reserves. Different approaches to the concepts of “uncertainty”, “risk”, and “reserve” have been considered. In the process of solving the set tasks on achieving the goal of the research, the scientific provisions have been worded, which serve as the ground for improving the accounting and the internal control of reserves at catering enterprises, what aims at ensuring the continuity of business activity of these companies.
Keywords: Catering enterprises; principle of business continuity; reserves.